Central Nervous System Activity of Syzygium cumini Seed - Kumar, A.; Padmanabhan, N.; Krishnan, M.R.V. (Pakistan Journal of Nutrition, 2007)
The Syzygium cumini (Myrtaceae) is a traditional medicine plant for the treatment of hypoglycemic, antibacterial, anti-HIV and antidiarrheal activities. The work reached the acute toxicity of Syzygium cumini and its action on the Central Nervous System (CNS) because no data in the literature have been found of pharmacological activity of this plant in the CNS. The seed was extracted with ethyl acetate and methanol and investigated for its Central Nervous System activity (CNS) of Albino mice in rota rod and actophotometer at the dose level of 200 mg/kg and 400 mg/kg. Both the extract exhibited significantly CNS activity. This study established CNS activity in Syzygium cumini seed.